Mental Health - Abstracts of Poster Presentations (Nepal Journal of Epidemiology, 2014)
Abstracts of the Poster Presentations at the session on Mental Health at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10168